Surgical Treatment of Type III Laryngotracheoesophageal Clefts: Techniques and Outcomes. (17th September 2021) - Kou, Yann‐Fuu; Redmann, Andrew; Smith, Matthew M.; Hart, Catherine K.; Rutter, Michael J.; de Alarcon, Alessandro
Abstract : Objectives/Hypothesis: Determine surgical and swallowing outcomes after surgery for type III laryngotracheoesophageal cleft (LTEC). Study Design: Case series with chart review. Methods: Chart review was performed on patients with type III LTEC between 2000 and 2019. Demographics, surgical outcomes, and swallowing outcomes were collected and analyzed. Results: Thirty‐three patients met inclusion criteria (28 open and 5 endoscopic repairs). Mean age was 3.4 years for the open group and 0.9 years for the endoscopic group. Seventeen (51.5%) patients had a syndromic diagnosis, most commonly Opitz syndrome and Trisomy 21. Mean follow‐up was 33.6 months. Thirteen (39.4%) patients had a previous repair attempt prior to repair at our institution. Twenty‐four (70.6%) patients had a tracheostomy prior to or at the time of surgical repair and 13 (38.2%) remain tracheostomy‐dependent. Nine patients (27.3%) required a revision cleft repair and four (12.1%) required two revisions. Thirty‐one patients had an intact repair at last follow‐up (93.9). Two patients died outside the hospital over a year after surgery. Preoperatively 13 of 17 patients with swallowing evaluations aspirated. After repair, 11 of 20 patients were deemed safe for all consistencies and seven were safe for thickened. Endoscopic approaches were performed during the last 2 years of the study and had significantly lower operative time (354.4 minutes vs. 171.5 minutes). Conclusions: Endoscopic and open approaches are effective for treatment of type III LTEC with 27.3% requiring revision and 93.9% of repairs intact at last follow‐up. Overall swallowing outcomes were good in patients who underwent postoperative instrumental swallow evaluation. Level of Evidence: 4 Laryngoscope, 132:1112–1117, 2022